1998
DOI: 10.1046/j.1432-1327.1998.2550081.x
|View full text |Cite
|
Sign up to set email alerts
|

Dimers of Thermus thermophilus elongation factor Ts are required for its function as a nucleotide exchange factor of elongation factor Tu

Abstract: Elongation factor Ts (EF-Ts) promotes the formation of active GTP-bound elongation factor Tu (EFTu) by accelerating the dissociation of GDP from the EF-Tu · GDP complex. Thermus thermophilus EFTs forms a dimer in solution, which is stabilised by interaction of a three-stranded antiparallel β-sheet from each of the two EF-Ts molecules. A disulfide bridge and several hydrophobic interactions are the main structural elements which stabilise the dimer [Jiang, Y., Nock, S., Nesper, M., Sprinzl, M. & Sigler, P. B. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…Crystal structures have revealed that the complex of Tt Tu/Ts is a heterotetramer, whereas the complex of Ec Tu/Ts is a heterodimer (29,30). Because Tt Ts dimer formation is required for its function as a nucleotide exchange factor (31), it would be expected that the monomeric Ec Ts would not function effectively with Tt Tu. However, based on the crystal structures, Tt Tu and Tt Ts interact through almost the same bipartite interface as that between Ec Tu and Ec Ts (29,30), and based on in vivo studies, Tt Tu has been suggested to participate in protein synthesis in E. coli (32).…”
Section: Discussionmentioning
confidence: 99%
“…Crystal structures have revealed that the complex of Tt Tu/Ts is a heterotetramer, whereas the complex of Ec Tu/Ts is a heterodimer (29,30). Because Tt Ts dimer formation is required for its function as a nucleotide exchange factor (31), it would be expected that the monomeric Ec Ts would not function effectively with Tt Tu. However, based on the crystal structures, Tt Tu and Tt Ts interact through almost the same bipartite interface as that between Ec Tu and Ec Ts (29,30), and based on in vivo studies, Tt Tu has been suggested to participate in protein synthesis in E. coli (32).…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial EF-Ts and eukaryotic EF-1 b, an analog of EF-Ts, are comprised of only one domain per polypeptide and have an approximate molecular weight of 30,000. It has been reported that dimerization of Thermus thermophilus EF-Ts is required for its nucleotide exchange function, in contrast with E. coli EF-Ts, which functions as monomers (Nesper et al, 1998). Perhaps chloroplast EF-Ts proteins also require dimerization for their function and that could be accomplished by having two EF-Ts domains in the same polypeptide.…”
Section: Discussionmentioning
confidence: 99%
“…SDM experiments showed than the hydrophobic interactions present in the Thermus enzyme made the dimer more resistant to dissociation (180, 250) (see "Hydrophobic Interactions" above). Mutagenesis of a hydrophobic core at the dimer interface in the T. thermophilus elongation factor EF-Ts showed that this hydrophobic core contributed to the enzyme dimerization and that dimer formation considerably contributed to the thermodynamic stability of T. thermophilus EF-Ts, (259). Methanopyrus kandleri formylmethanofuran:tetrahydromethanopterin (H 4 MPT) formyltransferase (MkFT) is monomeric and inactive at low salt concentrations.…”
Section: Intersubunit Interactions and Oligomerizationmentioning
confidence: 99%